Transmission network expansion planning considering repowering and integration of small-scale generation (2018)
ABSTRACT: This paper presents a new modeling approach for the transmission network expansion planning (TNEP) considering repowering of circuits and integration of small-scale generation. The TNEP consists on determining the new assets that will be needed in the network to meet a forecasted demand. Traditionally, the candidate solutions of this problem only consider the integration of new lines or transformers. In this paper we expand the candidate solutions to include repowering of circuits. Also, the integration of small-scale generation is considered. The TNEP problem is modeled as a mixed integer linear programming problem and solved using the software GAMS. Several tests are performed on the Garver system and IEEE 24 bus test system showing the applicability of the proposed model. Results show that circuit repowering in strategic corridors, combined with the installation of small-scale generation, contributes to a significant reduction of the cost of the TNEP.